2022
DOI: 10.3389/fncel.2022.905299
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Sodium-Dependent Glutamate Transporter GLT-1 in Maturing Oligodendrocytes Attenuates Myelination of Callosal Axons During a Postnatal Phase of Central Nervous System Development

Abstract: The sodium-dependent glutamate transporter GLT-1 (EAAT2, SLC1A2) has been well-described as an important regulator of extracellular glutamate homeostasis in the central nervous system (CNS), a function that is performed mainly through its presence on astrocytes. There is, however, increasing evidence for the expression of GLT-1 in CNS cells other than astrocytes and in functional roles that are mediated by mechanisms downstream of glutamate uptake. In this context, GLT-1 expression has been reported for both n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that myelin and axon defects are more prone to axons of specific caliber (Thomason et al, 2022). Therefore, we used a similar binning approach (increments of 0.1 μm) to assess axonal caliber‐specific pathologies; however, no difference in axon caliber, or myelin thickness was detected (data not shown).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported that myelin and axon defects are more prone to axons of specific caliber (Thomason et al, 2022). Therefore, we used a similar binning approach (increments of 0.1 μm) to assess axonal caliber‐specific pathologies; however, no difference in axon caliber, or myelin thickness was detected (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…To specifically target ablation of the Cst gene in oligodendrocytes in the CNS, we purchased Plp CreERT mice (Jax Labs; stock # 005975) to induce recombination and mated them to the homozygous Cst floxed (Cst fl/fl ) line. The PLP CreERT line was chosen as the Cre driver line since this line has been routinely used to efficiently induce adult-onset gene ablation in the CNS in chronic studies (Pillai et al, 2009;Mei et al, 2013;Jablonska et al, 2016;de Logu et al, 2017de Logu et al, , 2020Thomason et al, 2022;Borges et al, 2023). In the original report of the generation of these mice, Doerflinger et al, (2003) showed that in the absence of tamoxifen, Cre remained cytoplasmic and there was no evidence of recombination.…”
Section: Generation Of Cst Conditional Knockout Mousementioning
confidence: 99%
“…GraphPad Prism (GraphPad Software Inc.; ) was used for all statistical analyses. Prior sample calculations were not performed: sample size was estimated based on previous studies of a similar nature (Dennis et al, 2008; Lafrenaye & Fuss, 2011; Martinez‐Lozada et al, 2014; Thomason et al, 2022; Waggener et al, 2013; Wheeler et al, 2015). Data were assessed for normality using the Shapiro–Wilk normality test prior to analysis.…”
Section: Methodsmentioning
confidence: 99%